Evaluation and Analysis The CAPM and APT Models in Spanish Stock Market - Liang, Yue (2012)
Based on many previous studies about the assets pricing models and theories, the author makes a further development and research with the Spanish stock market. In this paper, the risk coefficient Beta is calculated and the square of Beta, kurtosis and skewness, total risk and unique risk are involved in the OLS regression model. On the other hand, Fama and French three-factor model and CNZ model are tested using Spanish stock data. Referring to the Fama and French’s investigation, we add more macroeconomic factors and firm characteristics factor in the APT models and carrying on the validity test. Finally we compare both the validity and efficiency of these models and make some suggestion for the Spanish investors.